Coronary risk factors in schoolchildren. Issue 2 (February 1993) - Boreham, C; Savage, J M; Primrose, D; Cran, G; Strain, J
Abstract : Death rates from coronary heart disease (CHD) in Northern Ireland are among the highest in the world. However, no data have been available to test the hypothesis that the high prevalence of CHD is reflected by the risk status of the childhood population. A randomly selected 2% population sample of 1015 children aged 12 and 15 years was studied to obtain baseline information on blood pressure, lipid profile, cigarette smoking, family history, physical activity, cardiorespiratory fitness, and dietary fat intake. Using available criteria thresholds, 15-23% displayed increased blood pressure, 12-25% had unfavourable lipid profiles, and 18-34% were overfat. In 15 year old children, 16-21% admitted being regular smokers, 26-34% displayed poor cardiorespiratory fitness, and 24-29% reported little physical activity in the previous week. Dietary analysis revealed relatively low polyunsaturated to saturated fatty acid ratios and high mean fat intakes, accounting for approximately 40% total daily energy. Despite the exclusion of family history from the analysis, 16% of the older children exhibited three or more risk factors. These results justify major concern about the level of potential coronary risk in Northern Ireland schoolchildren. Broadly based primary prevention strategies aimed at children are essential if future adult CHD mortality is to be reduced.